The Using of Scientific Based Physics Module in Learning to Enhance High School Students’ Critical Thinking Skills on Rotation Dynamics and Equilibrium of Rigid Body - Dhimas Nur Setyawan; Nonoh Siti Aminah; Sarwanto Sarwanto (Journal of Education and Learning (EduLearn), 2017)
The purpose of this study was to determine the effectiveness of using a scientific based physics module to improve high school students' critical thinking skills. This study is a quasi experimental study which uses two classes taken at random experiment consists of one class and the control class. Class experiments using the scientific study using scientific-based modules and classroom experiments using books that have been owned by students. Experimental class numbered 25 students and control class numbered 28 students. The research was conducted in the first half (one) Academic Year 2016/2017. The method used is the test method with a pretest-posttest design. Data were analyzed with quantitative and qualitative methods. Data were analyzed using a pretest form of the homogeneity test to find out that the experimental class and controls used homogeneous. Posttest results were analyzed using normality test to determine the normally distributed data, N-gain to determine the increase critical thinking skills, as well as test two parties not bound to determine whether or not there is a difference in the increase in critical thinking skills. Conclusions and recommendations are the use of scientifically-based modules effectively improve the ability to think critically and use physics-based scientific modules should be adjusted to the prevailing syllabus and curriculum so that learning can take place properly.